ANALISIS LABA KOTOR SEBAGAI SALAH SATU ALAT DALAM MENETAPKAN HARGA JUAL PADA PERUSAHAAN TELUR ASIN ENI JAYABREBES - Purwanto, Medi Tri (PERMANA, 2013)
The purpose of this research is: to know the methods of determining the selling price set by the company and setting the selling price set by the company. The method used is the case study company Eni Jaya regency, while the data collection methods used are surveys, interviews, questionnaires and research library. In analyzing the data using techniques seleisih gross profit, sales margin, the difference in cost of sales and net volume difference. From the analysis it can be concluded: (1) the difference shows the difference in the selling price is not profitable, which can becaused by unstable selling prices whencompared to other similar companies and the selling price is too high so as not to compete with other similar companies;(2) difference in sales volume showed an unfavorable difference, which dsebabkan by unfavorable product promotion that consumers´ purchasing power to decline to offer goods and Lack of purchasing power for goods offered; (3) the difference shows the difference in the cost of goods that are not profitable, due to rising production costs and the purchase of raw materials at a high price; (4) the difference shows the difference in the volume of goods that are not profitable, can be caused by the skillsof workers and the working hours are used effectively and efficiently; and (5) difference in the composition of sales showed a favorable difference, which may be caused by a number of products that were sold to cover products that can not be sold or sales decline. Implications: companies need to plan production budget more carefully and there needs to be consideration for production costs incurred on realization does not exceed budgeted amounts. Because of the high and low production costs also affect the high and low selling prices, so that in its pricing to compete with other companies.Keywords : Price , Profit , Selling Price Determination